ANALYSIS OF INTEGRATED BUS TERMINAL SERVICES IN PULO GEBANG IN INCREASING CUSTOMER SATISFACTION - Aswanti Setyawati; Muhammad Nur Huda; Suripno Suripno; Hendy Tannady (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2021)
This study aims to analyze the service level of the Pulo Gebang Integrated bus terminal in increasing customer satisfaction. Based on the analysis and discussion, the results of the gap analysis between customer perceptions and expectations of 22 service attributes are all negative (-) with a range of -0.15 to -1 , 49. This indicates that the quality of service is still far from customer expectations, the attributes of interest after analyzing with the Importance Performance Analysis, the priority for improvement is obtained as well as in an effort to improve the quality of customer service at the Pulo Gebang Integrated bus terminal, after analyzing the approach with the Quality Function Deployment method, seven order of priority improvement.